История для любознательных : 6-11 кл.: задачник : в 2 кн. (О. В. Кишенкова, М. В. Короткова) - Кишенкова Ольга Викторовна (1996)
Экземпляры: до (ретроконверсия) / Инвентарный номер: 33648 / Цена: 14150.00 / Сис.шифр: 63.3 / Авт.знак: К 46 / ГРНТИ: 03 / ББК: 63.3